Digital techniques for documenting and preserving cultural heritage - Bentkowska-Kafel, Anna,MacDonald, Lindsay (Arc Humanities Press, 2017)
This book presents interdisciplinary approaches to the examination and documentation of material cultural heritage, using non-invasive spatial and spectral optical technologies
12657/42785
Keywords: Historic preservation; Cultural property; Digital preservation; Digital Humanities; Museology & heritage studies; Conservation; restoration & care of artworks; Archaeological science; methodology & techniques; Archiving; preservation & digitisation